Eksistensi Koperasi Syariah di Kota Mataram - Muliani (TAFAQQUH, 2024)
This study aims to explore the implementation of Sharia principles in cooperatives as an alternative for communities transitioning to Sharia cooperatives in Mataram City, using a qualitative phenomenological approach. Through a descriptive-analytical method, this research focuses on collecting data from cooperative administrators, managers, and members selected through purposive sampling. Data were gathered through in-depth interviews, observation, and documentation, and then analyzed using data reduction, presentation, and conclusion techniques with credibility validation through triangulation. The results indicate that Sharia cooperatives operate based on principles of justice, transparency, prohibition of interest, and social responsibility, forming a profit-sharing business model oriented toward collective welfare. Additionally, the growth of Sharia cooperatives in Mataram is supported by government regulations and increasing market demand for Sharia-based financial services, prompting many conventional cooperatives to adopt the Sharia system. This research contributes to the development of Sharia economic policies and practices as an inclusive, sustainable business model that can enhance financial inclusion in society.